2009
DOI: 10.1016/j.molimm.2008.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Non-erythroid activities of erythropoietin: Functional effects on murine dendritic cells

Abstract: Erythropoietin (EPO) is the main hormone that promotes proliferation and differentiation of erythroid progenitor cells via binding to its surface receptor (EPO-R). Recent studies suggest that this hormone may affect also other cell types, besides the red blood cell lineage. We have previously demonstrated that the immune system is a target of EPO; however, the direct target cells of EPO, as well as the molecular mechanisms underlying its role as an immunomodulator, are unknown. Here we present evidence for fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
51
0

Year Published

2010
2010
2025
2025

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(56 citation statements)
references
References 60 publications
5
51
0
Order By: Relevance
“…Hence, such functions include neuroprotection (Brines et al 2004, Cilloni et al 2004, anti-neoplastic activity (Mittelman et al 2001, Katz et al 2005, and improvement in congestive heart failure (Silverberg et al 2002, Fiordaliso et al 2005, Camici et al 2007. We (Prutchi-Sagiv et al 2006a,b, 2008, Ghezzi & Mengozzi 2007, Katz et al 2007, Lifshitz et al 2009), as well as others (Ghezzi & Mengozzi 2007), have found EPO-associated improvement in immunological functions.…”
Section: Introductionmentioning
confidence: 62%
“…Hence, such functions include neuroprotection (Brines et al 2004, Cilloni et al 2004, anti-neoplastic activity (Mittelman et al 2001, Katz et al 2005, and improvement in congestive heart failure (Silverberg et al 2002, Fiordaliso et al 2005, Camici et al 2007. We (Prutchi-Sagiv et al 2006a,b, 2008, Ghezzi & Mengozzi 2007, Katz et al 2007, Lifshitz et al 2009), as well as others (Ghezzi & Mengozzi 2007), have found EPO-associated improvement in immunological functions.…”
Section: Introductionmentioning
confidence: 62%
“…Our search for possible mechanisms of the immunomodulatory effects of EPO led us to the novel discovery that dendritic cells express the EPO-receptor, and that stimulation with EPO enhances their survival and function. 7,8 Studies in murine models showed that EPO increased the splenic dendritic cell population with a higher cell surface expression of the co-stimulatory molecules CD80 and CD86. 8 Further analysis carried out on bone marrow-derived dendritic cells led to the findings that the cells expressed EPOreceptor mRNA and that in-vitro stimulation of these cells enhanced the cells' viability, up-regulated CD80, CD86 and MHC class II expression, augmented the secretion of interleukin (IL)-12 and activated multiple signaling pathways.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 Studies in murine models showed that EPO increased the splenic dendritic cell population with a higher cell surface expression of the co-stimulatory molecules CD80 and CD86. 8 Further analysis carried out on bone marrow-derived dendritic cells led to the findings that the cells expressed EPOreceptor mRNA and that in-vitro stimulation of these cells enhanced the cells' viability, up-regulated CD80, CD86 and MHC class II expression, augmented the secretion of interleukin (IL)-12 and activated multiple signaling pathways. 8 Based on these findings, we hypothesized that macrophages are also potential targets of EPO.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, PI3K/Aktpathway-related responses to OS and apoptosis have also been shown to be mediated by the transcriptional regulation of HO-1 [Martin et al, 2004]. Previously, Lifshitz et al demonstrated that the dendritic cells (DCs) are direct targets of EPO, to initiate the immune response through the overexpression of human EPO in transgenic mice in in vivo experiments and validate a higher expression of EPO-R mRNA from bone marrowderived DCs (BM-DCs) [Lifshitz et al, 2009]. Recent reports indicate that EPO exerts its cytoprotective effects in cardiac ischemia-reperfusion injury by inducing HO-1 expression [Burger et al, 2009] www.intechopen.com…”
Section: Cytoprotective Interaction Of Epo and Ho-1mentioning
confidence: 99%